2021
DOI: 10.1101/2021.07.26.21261155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wastewater surveillance for infectious disease: a systematic review

Abstract: Wastewater surveillance of SARS-CoV-2 has shown to be a valuable source of information regarding SARS-CoV-2 transmission and COVID-19 cases. Though the method has been used for several decades to track other infectious diseases, there has not been a comprehensive review outlining all of the pathogens surveilled through wastewater. The aim of this study is to identify what infectious diseases have been previously studied via wastewater surveillance prior to the COVID-19 Pandemic and identify common characterist… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 124 publications
0
7
0
Order By: Relevance
“…Meanwhile, they also need to monitor multiple diseases, even rare diseases. (22,23) A systematic review revealed that the major pathogens monitored in wastewater are infections with the families Picornaviridae, Adenoviridae, Calciviridae, Hepeviridae, and Reoviridae, three of which are known to contribute to diarrheal infections, (1) as shown in Figure 2. (1) Human pathogens discharged in substantial liquids were monitored to decide the source of natural agents in the sewer and the length of agent discharge.…”
Section: Wastewater-based Epidemiology (Wbe)mentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, they also need to monitor multiple diseases, even rare diseases. (22,23) A systematic review revealed that the major pathogens monitored in wastewater are infections with the families Picornaviridae, Adenoviridae, Calciviridae, Hepeviridae, and Reoviridae, three of which are known to contribute to diarrheal infections, (1) as shown in Figure 2. (1) Human pathogens discharged in substantial liquids were monitored to decide the source of natural agents in the sewer and the length of agent discharge.…”
Section: Wastewater-based Epidemiology (Wbe)mentioning
confidence: 99%
“…(22,23) A systematic review revealed that the major pathogens monitored in wastewater are infections with the families Picornaviridae, Adenoviridae, Calciviridae, Hepeviridae, and Reoviridae, three of which are known to contribute to diarrheal infections, (1) as shown in Figure 2. (1) Human pathogens discharged in substantial liquids were monitored to decide the source of natural agents in the sewer and the length of agent discharge. Diverse sources of biological agents in sewers are feces, pee, skin from the shower and hand washing, and saliva from respiratory discharges.…”
Section: Wastewater-based Epidemiology (Wbe)mentioning
confidence: 99%
See 1 more Smart Citation
“…Many pathogens are shed by infected individuals via stool, sputum, and/or from the skin, depending on the pathogen.This means pathogen particles can make it into wastewater when infected individuals use the toilet, brush their teeth, or shower. Previous studies have shown that a range of pathogens are detectable in wastewater samples (Xagoraraki and O’Brien 2020; Kilaru et al 2022). In regions where household wastewater is centrally collected, wastewater represents a pooled community sample and wastewater pathogen loads indicate community disease burden.…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater-based epidemiology (WBE) has attracted attention as an emerging outbreak surveillance tool due to its advantages, including flexibility, cost-effectiveness in sample collection, near real-time data, and capacity to provide a snapshot of an entire community’s health compared to traditional surveillance systems. Wastewater-based epidemiology is based on collecting relevant information from untreated sewage, through biological and/or chemical analyses to detect biomarkers associated with infectious diseases or environmental risk factors. , Because human excreta contain biomarkers indicative of multiple aspects of risks, raw sewage is an ideal source of information . As a result, WBE has been widely implemented for the detection of SARS-CoV-2, as well as illicit drug usage , and consumption of pharmaceuticals …”
Section: Introductionmentioning
confidence: 99%